PESTS OF MEDICINAL SAFFRON (CROCUS SATIVUS L.) IN SURKHONDARYO REGION AND THEIR CONTROL MEASURES - Akbutaev Azim Nuriddinovich; Khalmuminova Gulchehra Kulmuminovna; Mahkamova Nargiza Ergashaliyevna (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the medicinal properties of the saffron plant. Currently, as a result of pests and diseases causing great damage to agricultural crops, their quality and quantity are being damaged. Among them, spider mite, tobacco thrips, and aphids cause great damage to the saffron healing plant. It is recommended to use microbiological preparations against pests that harm the saffron medicinal plant.